ATIVIDADE FITOTÓXICA DE Guettarda Uruguensis (RUBIACEAE) SOBRE A GERMINAÇÃO E CRESCIMENTO DE SEMENTES DE LACTUCA SATIVA - Duarte, Ana Flávia Schvabe; Krause, Mariana Saragioto; Martins, Antonio Luiz da Costa; Miguel, Marilis Dallarmi; Miguel, Obdulio Gomes (Visão Acadêmica, 2018)
The study evaluates the phytotoxic activity of the ethanolic extract and its organic fractions obtained from the stem bark of the Guettarda uruguensis species Cham. & Schltdl. (Rubiaceae) on germination and seed growth of Lactuca sativa. The evaluated parameters were the rate of germination velocity, radicle and hypocotyl growth. The results obtained in the present study demonstrate that Guettarda uruguensis produces chemical compounds that act in the stimulation and inhibition of the seeds germination, the radicle growth and inhibition of the hypocotyl of the Lactuca sativa species.